Eccentric hamstring strength in young athletes is best documented when normalised to body mass: A cross-sectional study with normative data of 590 athletes from different age categories - Jeanguyot, Evan; Salcinovic, Benjamin; Johnson, Amanda; van Dyk, Nicol; Whiteley, Rod (Biology of Sport, 2023)
Despite its widespread use in adults, the Nordic hamstring exercise remains underexplored in athletic youth populations. Further, given the dynamic nature of growth and maturation, comparisons with elite adult populations may be inaccurate. Here we describe absolute and body mass-normalised eccentric hamstring normative values for football, athletics and multi-sport youth populations. 676 routine standardised tests were conducted, including 244 U12–U18 student-athletes (football, athletics, multi-sport) and 346 Qatar Stars League (QSL) football players using the NordBord. The average maximum values for the left and right leg from 3 repetitions were recorded. Significant increases in absolute strength were seen across chronological (e.g., 150 N±15 for U12 to 330 N±40 for U18) and skeletal (142.9 N±13.9 for skeletal age of 12 compared to 336.2 N±71.2 for skeletal age of 18) age groups. The differences in values normalised to body mass were smaller at 3.6 N/kg±0.25 for the U-13 group, but similar for the U14 to U18 groups (4.5 N/kg±0.16, 4.6 N/kg±0.11, 4.6 N/kg±0.27, 4.7 N/kg±0.14, 4.5 N/kg±0.18). Students displayed lower absolute strength than the professional football players (272.1 N compared to 297.3 N, p < 0.0001) but higher relative strength (4.7 N/kg compared to 4.2 N/kg, p < 0.0001). Comparing Nordic hamstring strength values between athletes, and between skeletal and chronological age groups can be done when values are normalised to the athlete’s body mass. For the U14s and onwards age categories, body mass normalised values are comparable to professional football players.